Pendampingan P5 dalam Peningkatan Kreativitas Dan Pencegahan Stunting Melalui Hidroponik Serta Produksi Kripik Bayam di SDN 013 Pulau Tengah - Purwanto, Hadi; Ihkram Mulya, Sejratul; Rira Almipa Suci Sefindra; Nur Rohmatulloh; Firmathoina, Aisyah (Jurnal Pengabdian UntukMu NegeRI, 2024)
This program focuses on implementing the Strengthening Pancasila Student Profile (P5) Project at SDN 013 Pulau Tengah, Pangean District, Kuantan Singingi Regency. Through hydroponic planting methods and the production of spinach chips, students in grades 4, 5 and 6 are invited to increase their creativity while participating in stunting prevention. This activity includes socialization about the importance of balanced nutrition, training in hydroponic planting using used materials, and processing harvests into economically valuable products, such as spinach chips which are rich in vitamin A. The results of the activities show an increase in students' understanding of nutrition, stunting, and their ability to implement them. modern agricultural technology. Apart from that, this program has also succeeded in developing students' entrepreneurial skills through the production and marketing of spinach chips products. This program not only contributes to strengthening skills-based education and entrepreneurship, but also plays a role in efforts to reduce stunting rates among children through the introduction of healthy and sustainable eating patterns.